Antibacterial activity of ethanolic extracts of Plantago major leaves against Pseudomonas aeruginosa from burn infections - Turki Monawer, Alaa'; Mohammed Abdulkahar Mammani, Ismaeil (The Journal of Infection in Developing Countries, 2023)
Introduction: The use of herbal extracts is increasing because of the increase in bacterial resistance to conventional antibiotics. Plantago major is frequently used in traditional medicine because of its medicinal properties. The aim of the current study was to assess the antibacterial efficacy of an ethanolic extract of P. major leaves against Pseudomonas aeruginosa isolated from burn infections. Methodology: One hundred and twenty burn samples were collected from hospitalized patients at the Burn Hospital in Duhok city. The bacterium was identified using Gram stain, colony morphology, biochemical tests and selective differential media. Antibacterial activity of P. major leaves was assessed by using an ethanolic extract in serial dilutions of 100, 75, 50, 25, and 10 % and disc diffusion assay. Antibiotic susceptibility testing was also performed by disk diffusion using Muller-Hinton agar medium. Results: Different concentrations of the ethanolic extract of P. major leaves exhibited different zones of inhibition against P. aeruginosa from 9.93 mm to 22.18 mm in diameter. The inhibition zone increased as the concentration of the extract increased. The 100% ethanolic extract had the greatest inhibitory effect, inhibiting bacteria in the zone of 22.18 mm diameter. This bacterium showed a high level of resistance to the antibiotics used. Conclusions: This study demonstrated that herbal extracts could be used as a combination therapy with antibiotics and chemical drugs in the elimination of bacterial growth. Further investigations and future experiments, need to be carried out before recommending use of herbal extracts.